A compact process for treating oilfield wastewater by combining hydrolysis acidification, moving bed biofilm, ozonation and biologically activated carbon techniques. Issue 9 (2nd May 2016) - Zheng, Tao
ABSTRACT: A lab-scale hybrid system integrating a hybrid hydrolysis acidification (HA) reactor, a moving bed biofilm reactor (MBBR) and an ozonation-biologically activated carbon (O3 -BAC) unit was used in the treatment of heavy oil wastewater with high chemical oxygen demand (COD) and low biodegradability. The effects of hydraulic retention time and ozonation time were investigated. The results show that under the optimal conditions, the effluent concentrations of COD, oil and ammonia were 48, 1.3 and 3.5 mg/L, respectively, corresponding to total removal efficiencies of 95.8%, 98.9% and 94.4%, respectively. The effluent could meet the grade I as required by the national discharge standard of China. The HA process remarkably improved the biodegradability of the wastewater, while the MBBR process played an important role in degrading COD. The ozonation process further enhanced the biodegradability of the MBBR effluent, and finally, deep treatment was completed in the BAC reactor. This work demonstrates that the hybrid HA/MBBR/O3 -BAC system has the potential to be used for the treatment of high-strength oilfield wastewater.